2006
DOI: 10.1577/t05-207.1
|View full text |Cite
|
Sign up to set email alerts
|

Bioacoustics of Fishes of the Family Sciaenidae (Croakers and Drums)

Abstract: The teleost family Sciaenidae, collectively known as the croakers and drums because of their propensity for making sound, includes roughly 70 genera and 270 species worldwide. Although many other groups of fish also communicate using sound, the sciaenids are unique in the diversity of their sound production mechanisms, variety of sounds produced, and structural variation in sound-detecting structures. This paper reviews the bioacoustics of sciaenid fishes, including mechanisms involved in the production and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
147
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 107 publications
7
147
0
1
Order By: Relevance
“…Seasonally, silver perch, oyster toadfish, and black drum began calling in early spring and ended in May; sound production of spotted seatrout began in late winter (February) and ended in early fall (end of September), and the majority of red drum sound production occurred in August and September (Montie et al 2015). These sound production timelines were consistent with the spawning timelines observed in other studies along the Southeast Atlantic coast and the Gulf of Mexico, which were based upon on the detection of courtship sounds, gonad indices, the presence of eggs and larvae in the water column, and/or appearance of young of the year (YOY) (Dobrin 1947, Tavolga 1960, Fish & Mowbray 1970 Monczak et al: Fish soundscape of an estuary Overstreet 1983, Fine et al 1984, Beckman et al 1988, Brown-Peterson et al 1988, McMichael & Peters 1989, Murphy & Taylor 1990, Saucier & Baltz 1993, Ross et al 1995, Sprague 2000, Brown-Peterson & Warren 2002, Nieland et al 2002, Roumillat & Brouwer 2004, Ramcharitar at al. 2006, Locascio & Mann 2008, Luczkovich et al 2008, Locascio & Mann 2011, Wall et al 2013, Montie et al 2015.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Seasonally, silver perch, oyster toadfish, and black drum began calling in early spring and ended in May; sound production of spotted seatrout began in late winter (February) and ended in early fall (end of September), and the majority of red drum sound production occurred in August and September (Montie et al 2015). These sound production timelines were consistent with the spawning timelines observed in other studies along the Southeast Atlantic coast and the Gulf of Mexico, which were based upon on the detection of courtship sounds, gonad indices, the presence of eggs and larvae in the water column, and/or appearance of young of the year (YOY) (Dobrin 1947, Tavolga 1960, Fish & Mowbray 1970 Monczak et al: Fish soundscape of an estuary Overstreet 1983, Fine et al 1984, Beckman et al 1988, Brown-Peterson et al 1988, McMichael & Peters 1989, Murphy & Taylor 1990, Saucier & Baltz 1993, Ross et al 1995, Sprague 2000, Brown-Peterson & Warren 2002, Nieland et al 2002, Roumillat & Brouwer 2004, Ramcharitar at al. 2006, Locascio & Mann 2008, Luczkovich et al 2008, Locascio & Mann 2011, Wall et al 2013, Montie et al 2015.…”
supporting
confidence: 87%
“…Sound production in these fishes typically involves rapid movement of the sonic muscle surrounding the swim bladder. The resulting calls are species-specific due to anatomical differences in swim bladder and sonic muscle morphology as well as neural programming; therefore, call types can be used for species identification (Winn 1964, Ramcharitar et al 2006.…”
Section: Design By Tim Devine Uscb Graphics Managermentioning
confidence: 99%
See 2 more Smart Citations
“…From a functional point of view, otoliths are associated with hearing and the sense of balance (Popper and Coombs 1982;Ramcharitar et al 2006;Schulz-Mirbach et al 2014). Numerous studies have demonstrated that otolith morphology, including the sulcus acusticus, is also linked to swimming Echeverría 2003, Volpedo et al 2008), feeding , spatial distribution (Gauldie and Crampton 2002;Lombarte and Cruz 2007;Sadighzadeh et al 2014) and acoustic communication (Popper and Lu 2000;Cruz and Lombarte 2004).…”
Section: Introductionmentioning
confidence: 99%